Analisis Persaingan Antara Brand Teh Pucuk Harum dan Teh Botol Sosro - Agum W.P, Muhamad; Zaidan N.H, Muhamad; Hidayat, Syamsul (PT Maju Malaqbi Makkarana, 2023)
Increased consumer demand for packaged tea has created various local and international business actors who are trying to meet people's needs. Packaged tea drinks are now the main choice in Indonesia after brewed tea, especially among urban people who prefer a practical and efficient lifestyle. In facing this trend, marketers need to have a deep understanding of current consumer behavior. It is important for marketers to understand consumers' needs, tastes and decision-making processes in order to produce products that meet their expectations. This research aims to explore the value of independent variables, be it one variable or more, without making comparisons or making connections between variables. The research method used is descriptive quantitative, where variables are described objectively according to reality, supported by data in the form of numbers resulting from measurements. Based on data analysis, it can be concluded that the research population came from undergraduate Management Studies students at Bina Bangsa University, totaling 4,091 people. Based on the results of the analysis, it is recommended to develop a more effective marketing strategy, especially regarding the influence of Pucuk Tea on purchasing decisions. Include other factors that might influence the Y variable to improve the accuracy of the analysis and research results.